Explosive Compaction of Foundation Soils for the Seismic Upgrade of the Seymour Falls Dam - Ron Elliott; Lewis Clarke; Blair Gohl; Ed Fulop; Neil Singh; Frank Huber (International Society of Explosives Engineers, 2009)
This paper covers the successful application of explosive compaction technology for the densification of the foundation soils for the seismic upgrade of the Seymour Falls Dam, Vancouver, BC. The original earthfill embankment constructed during 1958 to 1961 was upgraded in 2004 to 2007 to withstand the effects of a maximum credible earthquake. This paper provides general background information on the theory of the explosive compaction of soils, history of use, geology of the site, project constraints, explosives selection, blast designs, instrumentation used, problems encountered and solutions implemented, and the results achieved.